Against the ‘Control Argument’: Assessing the State’s Authority in the State-Commissioned Qur’ān Translation - Lukman, Fadhli (Islamic Studies Review, 2023)
Indonesia is one of a few countries that has an official Qur’ān translation, namely Al-Qur’an dan Terjemahnya (QT). As a country that has always been preoccupied with issues of religious regulation, there is a general consensus among the current scholarship on QT, namely that QT is the state's instrument for creating a standardized Islamic discourse in Indonesia. My paper questions this argument through an analysis of three interpretive cases in QT: the creation verse (Q 4:1), akābīra mujrimīhā in Q 6:123, and awliyāʾ in Q 5:51, focusing on the extent to which the interpretive outcome of QT is closely controlled by the state. In contrast to the 'control argument,' this study demonstrates that the renderings of QT in these three cases reflect the state's lack of involvement in the actual translation process. Despite the fact that QT is a state-commissioned and authorized Qur’ān translation, the ulama continue to be the masters of QT interpretive authority. While the entire process of producing QT may imply the obvious presence of the state, when we consider the genealogical nature of tafsīr, the religious authority of QT returns to the ulama rather than the state.